UPAYA PENCEGAHAN PENYAKIT MENULAR MELALUI EDUKASI DAN TINDAKAN PREVENTIF BERBASIS MEDIA FLASH CARD GAME PADA SISWA SDN 04 GAUNG PADANG - Masrizal Masrizal; Ane Dayu Perwati; Yudi Pradipta; Falah Fauzi (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
State Elementary School (SDN) 04 Gaung in Padang City is within the working area of the Mata Air Community Health Center, which has a high record of infectious disease cases among children, such as diarrhea and dengue fever (DF). The school environment faces sanitation challenges, with open drains and standing water during rainfall, which increase the risk of disease transmission. This activity aims to enhance students' understanding of infectious disease prevention through education using flash card game media. The program employed a pre-test and post-test design, involving 19 students from grades 4 and 5. The intervention consisted of education using flash card games containing information about Clean and Healthy Living Practices (PHBS). Data were analyzed using the Wilcoxon test to measure changes in knowledge, attitudes, and behaviors before and after the intervention. There was a significant improvement in all measured variables: knowledge (p=0.000) with an average increase from 3.16 to 6.84, attitude (p=0.034) from 6.32 to 6.68, and behavior (p=0.003) from 4.58 to 5.58. The majority of participants were female (63.2%) and 10 years old (52.6%). Education through flash card games proved effective in increasing knowledge, attitudes, and behaviors of SDN 04 Gaung students regarding infectious disease prevention. This interactive learning method successfully created a fun and informative learning environment for students.